Obtenção de agentes diagnósticos a base de nióbio contendo íons lantanídeos - Moscardini, Susane Bonamin (2021)
The development of new diagnostic imaging agents can recognize tissue, organs, and pathologies with contrasting properties. So, studies in this area encourage the medical fields due to important factors like their efficiency, present low toxicity, and biocompatibility. These advantages an important in the diagnosis, prognosis, and treatment of various diseases by the low cost, deep penetration, high resolution, easier image processing, magnetic resonance imaging and X-ray computed tomography imaging, receiving significant attention at research and practice. On the other hand, near-infrared (NIR) fluorescent probes offer advantages like higher sensitivity, reasonably high photon penetration, low light scattering, and minimal autofluorescence from living tissues. Thus, this project aimed the synthesis and characterization of nanoparticles based on niobium IV oxide doped with lanthanides ions (Ln3+, where Ln3+ = Dy3+ or Gd3+ or La3+, Tm3+, Yb3+, and Nd3+) for the development of new multimodal materials with applications in the medical imaging field. Analyzing the structure and luminescence of materials, it observed that the samples doped with Gd3+/Dy3+, Tm3+ and Yb3+ ions presented better behavior at Yb3+ ions variation concentration, especially between 15.0 to 20.0% that favor the tetragonal phases of ytterbium III niobate YbNbO4 (PDF# 32-1421). In the luminescence spectra, the samples doped with Yb3+ ions presented thulium III higher emission at infrared region, 810 nm, being interesting the application of image diagnostic. Keywords: contrast agent, magnetic resonance, upconversion.